Bermedia Sosial dalam Perspektif Maqashid Syari'ah (Membangun Komunikasi di Media Sosial Berdasarkan Etika) - Iffatin Nur; Muhammad Ngizzul Muttaqin (Palita: Journal of Social Religion Research, 2020)
Abstrak[English]: Millennial era is always synonymous with the advancement of various lines of technology, including the development of modern telecommunications tools that lead to social media activities. Different groups almost enjoy today’s social media activities without exception. However, the impact of social media activities has led to various aspects of positive progress as well as an effect on harmful elements in the form of mutual ridicule, hoax news, and so forth. Maqashid syari’ah as the final value of the provisions of the Islamic law that carries the amount of protection of personal interests and the public interest is expected to be a response to social media activities today. As a literature-based study and literature review, this paper is expected to be able to contribute ideas and provide a solution to the various negative impacts of social media activities that occur at this time.Abstrak[Indonesia]: Era milenial selalu identik dengan kemajuan berbagai lini teknologi, tidak terkecuali berkembangnya alat telekomunikasi modern yang menimbulkan aktivitas media sosial. Aktivitas media sosial hari ini hampir dinikmati oleh berbagai kalangan tanpa terkecuali. Namun demikian, dampak dari aktivitas media sosial telah menimbulkan berbagai aspek kemajuan yang positif maupun berdampak pada aspek negatif berupa saling mencemooh, berita hoax dan lain sebagainya. Maqashid syari’ah sebagai nilai akhir dari ketentuan hukum Islam yang mengusung nilai perlindungan terhadap kepentingan pribadi dan kepentingan umum diharapkan bisa menjadi sebuah respon atas aktivitas bermedia sosial hari ini. Sebagai kajian berbasis literatur dan kajian pustaka, tulisan ini diharapkan mampu memberikan sumbangan pemikiran dan memberikan sebuah solusi atas berbagai dampak negatif dari aktivitas media sosial yang terjadi saat ini.